دراسة تحسين خواص أقمشة الصوب الزراعية المنتجة بأسلوب تريكو اللحمة - أبو العزم، أماني مصطفى بيومي; شلبي، هبا عبدالعزيز; محمد، مصطفى حمزة محمد; عبدالوهاب، نور عفيفي حسن عصر (المؤسسة العربية لإدارة المعرفة, 2024)
الأداء الوظيفي لأقمشة الصوب الزراعية يعتمد على ما يتوفر فيها من الخواص الميكانيكية والطبيعية التي تلائم هذا الأداء وتتغير هذه الخواص طبقا لتغيير قطر الخيوط ولونها والجوج، وأقمشة الصوب الزراعية تختلف في أدائها الوظيفي نتيجة توفير نسب تظليل متعددة وتغيير درجة حرارة وبالتالي إعطاء درجة التدفئة المطلوبة لبعض النباتات حسب الأقطار والألوان المختلفة ونوعين من الجوج. ويتم في دراسة هذا البحث دراسة مدى تأثير القطر واللون والجوج على بعض الخواص الوظيفية للأقمشة المنتجة مثل نسبة التظليل ودرجة الحرارة والرطوبة النسبية ونقطة الندى وقوة الشد والاستطالة، حيث يهدف البحث إلى الحصول على أنسب العينات التي تحقق أفضل الخواص الوظيفية وذلك عن طريق إنتاج (۱۸) عينة من الأقمشة باستخدام ثلاث أقطار والمستخدم ١٦٥ و185 و۲۱۰ ميكرون والألوان المختلفة مثل الأسود والأخضر والأبيض التي تعطي انعكاسات للضوء بنسب مختلفة ومع تغيير الجوج المستخدم وإنتاج عينات على جوج ١٠ أو جوج ۱۲، وتم إجراء عدد من الاختبارات لقياس الخواص الطبيعية والميكانيكية على العينات محل الدراسة وفق المواصفات القياسية مستخدمين خامة البولي ايثيلين بنمر متعددة ميكرون ١٦٥ و185 ميكرون و۲۱۰ ميكرون لعمل عدد من العينات ب ٢ جوج مختلفين وهم جوج ۱۰ وجوج ۱۲ وإنتاجهم على ماكينة تريكو اللحمة الدائري بعدد 3 ألوان مختلفة اللون الأسمر واللون الأبيض واللون الأخضر بنسب تظليل مختلفة وإجراء اختبار قياس درجة الحرارة عليهم. The functional performance of greenhouse fabrics depends on what is available in them of mechanical and natural properties that are suitable for this performance, and these properties change according to changing the diameter of the threads, their color, and the gauge. Greenhouse fabrics differ in their functional performance as a result of providing multiple shading percentages and changing the temperature, thus giving the degree of heating required for some plants according to different diameters, colors and two types of weather. In the study of this research, the effect of diameter, color, and gauze on some of the functional properties of the produced fabrics, such as the percentage of shading, temperature, relative humidity, dew point, tensile strength, and elongation, is studied. The research aims to obtain the most appropriate samples that achieve the best functional properties, by producing (18) A sample of fabrics using three diameters, and the user used 165, 185, and 210 microns, and different colors such as black, green, and white, which give reflections of light in different proportions, and with the change of the used gauge, samples were produced on 10 or 12 gauge, and a number of tests were conducted to measure the natural and mechanical properties of the samples under study according to Standard Specifications. The scientific experiment for research is: The use of polyethylene material with multiple microns of 165, 185 micron and 210 microns to make a number of samples with 2 different gauges, namely 10 and 12 gauge, and produce them on a circular weft knitting machine in 3 different colors, brown, white and green with different shading percentages, and conduct a temperature measurement test on them.
Keywords: الصناعات النسجية -- الصوب الزراعية -- التصميمات الوظيفية -- تقنية التريكو -- الحماية الزراعية